(untitled) (Research, Society and Development, 2025)
This technical report aims to present the results obtained from the accounting, tax, and managerial analysis of the company J M C LIMA LTDA, created as a case study for the Supervised Internship of the Accounting Sciences course at UNITINS. The company, with the trade name Strike Zone Boliche, was designed to operate in the segments of manufacturing sports equipment, food services, and leisure, with a focus on operating bowling alleys. The accounting and tax bookkeeping were performed using the Domínio system, including the registration of invoices, tax calculation, and the generation of ancillary obligations such as SPED, DCTFWeb, and eSocial. The financial statements (Income Statement and Balance Sheet) were prepared, followed by vertical and horizontal analyses, which showed asset growth, good liquidity, and positive profitability. The financial indicators demonstrated that the company has a solid structure and the capacity to generate results. The market analysis indicated that the bowling segment has low competition in the region, representing a strategic opportunity. In the commercial sector, differentiation will be required to compete with already established companies. In the industrial branch, there is also no strong regional competition, which characterizes a good growth opportunity. It is concluded that J M C LIMA LTDA shows economic viability and growth potential, provided that it maintains strict control over costs, efficient tax management, and strategic positioning in the regional market.